Efektivitas Komunikasi Pendamping Corporate Social Responsibility (CSR) - Yara Falmira Dianira (Departemen Sains Komunikasi dan Pengembangan Masyarakat, Fakultas Ekologi Manusia, IPB, 2020)
ABSTRACT An important factor for the success of a CSR program is effective communication. Communication will be effective if it has an impact. If the information is conveyed based on the needs, then the communication will be effective. This study aims to analyze the factors which are related to the effectiveness of CSR communication. This study used a census method to approach 37 participants who received CSR programs. The Data analysis used the Spearman rank correlation for the statistical tests. The results showed that there was a correlation between factors that have the strength of CSR companion communication (level of attractiveness of the companion, quality of message content, and sources of information) which have real communication at the level of understanding of the participants of the Kertajaya Creative Destination (KCD) CSR program. In addition, there is a real correlation the factors that have the strength of CSR companion communication (the level of credibility of the companion, the source information, and the level of the recipient) and having communication at the level of attitudes of participants in the Kertajaya Creative Destination (KCD) CSR program. However, there is no real correlation between CSR companion communication factors and participant actions.Keywords :communication effectiveness, CSR, elements of communication. ABSTRAK Faktor penting dari keberhasilan program CSR adalah komunikasi yang efektif. Komunikasi dikatakan efektif jika menimbulkan dampak. Bila informasi tersampaikan sesuai dengan kebutuhan, maka komunikasi yang dijalankan efektif. Penelitian ini bertujuan untuk menganalisis efektivitas komunikasi pendamping CSR. Penelitian ini menggunakan pendekatan sensus terhadap 37 orang peserta penerima program CSR. Analisis data menggunakan uji statistik korelasi rank Spearman. Hasil penelitian menunjukkan bahwa terdapat hubungan nyata antara faktor efektivitas komunikasi pendamping CSR (derajat daya tarik pendamping, kualaitas isi pesan, dan sumber informasi) dengan efektivitas komunikasi pada tingkat pemahaman peserta program CSR Kertajaya Creative Destination (KCD). Selain itu, terdapat hubungan nyata antara faktor efektivitas komunikasi pendamping CSR (tingkat kredibilitas pendamping, sumber informasi, dan tingkat penerima) dengan efektivitas komunikasi pada tingkat sikap peserta program CSR Kertajaya Creative Destination (KCD). Namun, tidak terdapat hubungan nyata antara faktor efektivitas komunikasi pendamping CSR dengan tindakan peserta. Kata Kunci : CSR, efektivitas komunikasi, unsur-unsur komunikasi.